Marketing analysis to improve market of hungaricums in the South-Alföld region - Nótári, Márta; Hajdu, Istvánné (Acta Agraria Kaposváriensis, 2005)
In our research we wanted to know what to do in order to increase the sale of hungaricums that are produced in the South Alföld region. Before developing a marketing strategy we always have to make a real positioning. That is why we examined the strength, weakness, threats and opportunities of the hungaricum products and the region. The region has special products: cherry from Kecel, onion from Makó, red pepper from Kalocsa. It has outstanding traditional methods of production: plum brandy from Békéscsaba, honey made from Asclepias syriaca, apricot brandy from Kecskemét. Despite the excellent quality packaging, branding and advertisement activity are on a low level. With markers of origin and the application of mediamix the demand for these products could be increased. It is the region’s duty to develop a positively differential image for his products, partly because the competition between the Hungary and the regions of the surrounding countries is getting fiercer and, on the other hand, this is the way to get to more domestic and international resource.
Keywords: Hungaricums; Region marketing; SWOT analysis